2015
DOI: 10.1177/0971523117695143
|View full text |Cite
|
Sign up to set email alerts
|

Health Financing in South Asia—The Role of Public–Private Partnerships

Abstract: Millions of households are pushed into poverty every year because of high out-of-pocket (OOP) expenditure on health care. Globally, each year more than 150 million people face financial catastrophe and around 100 million suffer destitution due to OOP payments made for health care. More than 90 per cent of these people reside in low-income countries. In South Asia, impoverishment due to health payments is significant with at least 32 million people in India alone being pushed into poverty annually due to OOP ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The role and importance of human capital for the sustained long-run economic growth has received increasing attention, though in recent past (Baldacci et al, 2008; Hye, 2002; Mundle, 1998; Romer, 1990). An increasing number of empirical studies confirm the positive impact of investment in human capital on productivity and growth (Behrman, 1990; Razvi et al, 2015). Moreover, a fatal attack on GDP as a narrow and inadequate measure of human welfare has led to the prominence of social indicators (Mundle, 1998; Sen, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The role and importance of human capital for the sustained long-run economic growth has received increasing attention, though in recent past (Baldacci et al, 2008; Hye, 2002; Mundle, 1998; Romer, 1990). An increasing number of empirical studies confirm the positive impact of investment in human capital on productivity and growth (Behrman, 1990; Razvi et al, 2015). Moreover, a fatal attack on GDP as a narrow and inadequate measure of human welfare has led to the prominence of social indicators (Mundle, 1998; Sen, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored various determinants of ANC visits at the individual, household and community levels in developing countries. Razvi and Khan (2017) pointed out that the health sector’s efficiency is influenced by such factors as hygiene and sanitation, nutrition, education and skills, poverty and deprivation, social practices, environment and pollution and many others. Kyei et al (2012) found that distance to healthcare services is the main obstacle to ANC visits at times of urgency.…”
Section: Introductionmentioning
confidence: 99%